KRAS G12C inhibition enhances efficacy to conventional chemotherapy in KRAS-mutant NSCLC - Tubita, Alessandro; Fancelli, Sara; Anela, Lorenzo; Petroni, Giulia; Caliman, Enrico; Mazzoni, Francesca; Scolari, Federico; Napolitano, Brunella; Menicacci, Beatrice; Comin, Camilla Eva; Voltolini, Luca; Pillozzi, Serena; et al. (Frontiers in Oncology, 2025)
Despite recent therapeutic advances, the adjuvant treatment of non-small cell lung cancer (NSCLC) remains a challenge. Reducing the risk of recurrence is still a concern, especially in the KRAS G12C population, for which platinum-based adjuvant chemotherapy (CT) remains the gold standard. In this study, we evaluated the efficacy, in terms of cell viability and volumetric reduction, of adding KRAS inhibitors (KRASi) sequentially or concurrently to CT in both parental (PR) and gemcitabine-resistant (GR) KRAS mutated NSCLC cell lines (SW1573 and H23). We demonstrated that KRASi added to CT (both sequential and concurrent treatment strategies) reduced cell viability in SW1573-PR and H23-PR and this effect is less evident in GR cell lines. Interestingly, in the 3D model, the concomitant use of KRASi+CT reduced spheroid volume in both PR and GR spheroids. Our results indicate that KRASi enhances the efficacy of CT in both NSCLC PR and GR cells, suggesting a potential therapeutic strategy to overcome chemoresistance in the adjuvant setting of NSCLC.